The Impact of Different Colors of Light-Emitting Diodes on Cacti Germination and Seedling Growth - Chamaiporn Anuwong; Kittiphan Ritthidechrat (ASEAN Journal of Scientific and Technological Reports, 2025)
To identify suitable light colors to break seed dormancy and enhance the growth of cactus seedlings. A short photoperiod and less light intensity affect seedlings, resulting in low germination and slow growth. Four cacti species are A. asterias, E. grusonii, M. geometrizans, and T. alonsoi, commonly grown as ornamental plants. The completely randomized design was experimental. The plant was cultured under the five different colors of light-emitting diodes (LEDs): natural light (NL), red, blue, green, and white LED, providing light for 12 hours/day. The results found that all cactus seeds can absorb water and have more than 50% viability, except for E. grusonii. The seed germination (%G) increased in NL and various colors of LED. White LED had the highest %G in A. asterias, but green LED had the highest α-amylase activity. In E. grusonii, M. geometrizans, and T. alonsoi, %G and α-amylase activity were the highest under red LED. In addition, all four cacti species had the lowest mean germination time under red LED. The growth of A. asterias and M. geometrizans had the highest seedling vigor, stem diameter, plant height, and root length under NL. They had the highest chlorophyll a and chlorophyll b. In E. grusonii and T. alonsoi under NL, with the highest stem diameter, plant height and increases chlorophyll a and chlorophyll b. However, white light has the maximum root length and seedling vigor. Thus, red, green, and white LEDs effectively break seed dormancy, while white LEDs stimulate cactus growth as the natural light.
Keywords: Botanical Research and Applications; Marine and coastal plant biology